The Effectiveness and Safety of Commonly Used Injectates for Ultrasound-Guided Hydrodissection Treatment of Peripheral Nerve Entrapment Syndromes: A Systematic Review - Buntragulpoontawee, Montana; Chang, Ke-Vin; Vitoonpong, Timporn; Pornjaksawan, Sineenard; Kitisak, Kittipong; Saokaew, Surasak; Kanchanasurakit, Sukrit (Frontiers in Pharmacology, 2021)
Background: Peripheral nerve entrapment syndromes commonly result in pain, discomfort, and ensuing sensory and motor impairment. Many conservative measures have been proposed as treatment, local injection being one of those measures. Now with high-resolution ultrasound, anatomical details can be visualized allowing diagnosis and more accurate injection treatment. Ultrasound-guided injection technique using a range of injectates to mechanically release and decompress the entrapped nerves has therefore developed called hydrodissection or perineural injection therapy. Several different injectates from normal saline, local anesthetics, corticosteroids, 5% dextrose in water (D5W), and platelet-rich plasma (PRP) are available and present clinical challenges when selecting agents regarding effectiveness and safety. Aims: To systematically search and summarize the clinical evidence and mechanism of different commonly used injectates for ultrasound-guided hydrodissection entrapment neuropathy treatment Methods: Four databases, including PubMed, EMBASE, Scopus, and Cochrane were systematically searched from the inception of the database up to August 22, 2020. Studies evaluating the effectiveness and safety of different commonly used injectates for ultrasound-guided hydrodissection entrapment neuropathy treatment were included. Injectate efficacy presents clinical effects on pain intensity, clinical symptoms/function, and physical performance, electrodiagnostic findings, and nerve cross-sectional areas. Safety outcomes and mechanism of action of each injectate were also described. Results: From ten ultrasound-guided hydrodissection studies, nine studies were conducted in carpal tunnel syndrome (CTS) and one study was performed in ulnar neuropathy at the elbow. All studies compared different interventions with different comparisons. Injectates included normal saline, D5W, corticosteroids, local anesthetics, hyaluronidase, and PRP. Five studies investigated PRP or PRP plus splinting comparisons. Both D5W and PRP showed a consistently favorable outcome than those in the control group or corticosteroids. The improved outcomes were also observed in comparison groups using injections with normal saline, local anesthetics, or corticosteroids, or splinting. No serious adverse events were reported. Local steroid injection side effects were reported in only one study. Conclusion: Ultrasound-guided hydrodissection is a safe and effective treatment for peripheral nerve entrapment. Injectate selection should be considered based on the injectate mechanism, effectiveness, and safety profile.